Modeling and modern control of wind power - Wu, Qiuwei; Sun, Yuanzhang, 1954- (John Wiley & Sons, Inc., 2018)
This book covers the modeling of wind power and application of modern control methods to the wind power control--specifically the models of type 3 and type 4 wind turbines. The modeling aspects will help readers to streamline the wind turbine and wind power plant modeling, and reduce the burden of power system simulations to investigate the impact of wind power on power systems. The use of modern control methods will help technology development, especially from the perspective of manufactures.
Keywords: Wind power -- Mathematical models.; Wind power plants.; Wind turbines.; Windmills.; elektronické knihy; electronic books